The Portrait of Lecturer’s Feedback on Students’ Oral Presentation Experience from Indonesian and Nepal University - Bansa, Yorina An’guna (PPSDP International Journal of Education, 2023)
Although much research has been conducted on teacher feedback, little is discussed about how teacher educators give feedback on student teachers’ oral presentations to improve students’ communicative competence in foreign-language (FL) education. Semi-structured interviews have been carried out to get the data and this case study analyzed the methods used by an experienced Indonesian teacher educator of English as a foreign language to provide feedback on student teachers’ oral presentation tasks. This study revealed that the teacher gave feedback mainly focused on content, oral skill development, and analytical thinking. The analysis also revealed that the teacher used the pattern of ‘praise and suggestion’ when giving feedback on student teachers’ oral presentations. This paper also discusses relevant pedagogical implications for student teacher’s feedback practices in the EFL context.